Efeito neuroprotetor e antiepiléptico da infusão intracerebroventricular crônica de angiotensina-(1-7) em ratos com epilepsia do lobo temporal - Gomes, Karina Pereira (2020)
Epilepsy is a severe neurological disorder characterized by permanent predisposition of the brain to generate spontaneous and recurrent seizures. Temporal Lobe Epilepsy (TLE) is the most frequent type of epilepsy in adults and is often refractory to pharmacological treatments available. Recently, several neuropeptides and their receptors have been suggested as promising therapeutic targets for the treatment of epilepsy, including neuropeptides and receptors of the Renin Angiotensin System (RAS). The aim of this study was to evaluate the effects of chronic treatment with Angiotensin-(1-7) (Ang-(1-7)) in male Wistar rats with TLE. The Pilocarpine (PILO) model was used for TLE induction and after the first spontaneous seizure, the animals were submitted to stereotactic surgery for implant of a guide cannula attached to an osmotic minipump. Rats of control group (CT) underwent the same procedures as the rats of groups with epilepsy, but were resistant to PILO model, not developing ELT. Intracerebroventricular infusion of Ang-(1-7) (200ng/kg/h) or sterile saline solution (NaCl 0.9%) was performed for 30 days and body weight, feed intake and spontaneous seizures were evaluated. At the end of the treatment, behavioral tests were performed in Elevated Plus Maze (EPM) and Open Field (OF) for evaluation of anxiety-like behavior and locomotor/exploratory activity. In the next day after behavioral tests, the animals were euthanized and the hippocampus were dissected, stored and later processed for protein analysis using Western Blot technique. For RAS components investigation, protein levels of Angiotensin Converting Enzyme 2 (ACE2) and Neutral Endopeptidase (NEP), as well as AT1, AT2 and Mas receptors were evaluated. In addition, hippocampal levels of Interleukin-6 (IL-6), Superoxide Dismutase (SOD), Catalase (CAT), B-Cell Lymphoma 2 (Bcl-2) and the phosphorylation of Mammalian Target of Rapamycin (mTOR) were quantified. Chronic intracerebroventricular treatment with Ang-(1-7) significantly reduced the frequency of spontaneous epileptic seizures, mainly at light photoperiod of the light-dark cycle, without changing its duration. Saline treated TLE rats (EP) showed significantly lower body weight gain than control rats without epilepsy (CT), which was attenuated in the last two weeks by Ang- (1-7) treatment (EP + Ang-(1-7)). However, the feed intake did not differ among evaluated groups. The time spent in EPM open arms by EP group was significantly higher than CT group, an effect attenuated by Ang-(1-7) treatment. In addition, the total number of entries in EPM arms was higher in EP group, which was reversed in EP + Ang-(1-7) group. The number of crossings in OF was significantly higher in EP group, which was reversed by Ang-(1-7) treatment. However, the immobility time and the numbers of rearing, also increased in the EP group, were only attenuated by Ang-(1- 7) treatment. Our results, revealed that Ang-(1-7) positively regulated the antioxidant protein CAT, the anti-apoptotic protein Bcl-2 and also increased the phosphorylation of anti-apoptotic protein mTOR, all reduced by epilepsy in hippocampus. In addition, the upregulation of AT1 receptor induced by TLE in hippocampus was also attenuated by treatment with Ang-(1-7). The protein levels of ACE2, NEP and SOD enzymes, as well as AT2 receptor and IL-6 were not statistically different between the groups. Mas receptor was downregulated in hippocampus of EP + Ang-(1-7) group. Our data suggest that Ang-(1-7) has direct modifying effects on chronic TLE by reducing oxidative stress and hippocampal neuronal death. From these results we can conclude that chronic intracerebroventricular treatment with Ang-(1-7) in rats with PILO induced- TLE reduces hippocampal neuronal damage and the frequency of spontaneous seizures, attenuating the damage in body weight gain and behavioral abnormalities. This study provides evidence that Ang-(1-7) and its receptor are promising targets for the treatment of TLE and its comorbidities.